Breastfeeding, schooling, and income: Insights from the Indonesian Family Life Survey. Issue 1 (4th September 2018) - Lutter, Randall; Ruhm, Christopher; Lin, Dajun; Liu, Siying
Abstract: Recent research has highlighted associations of breastfeeding with IQ, schooling, and income, but uncertainty about such links remains. The Indonesian Family Life Survey, representative of 83% of the Indonesian population, provides data on breastfeeding, parents' years of schooling, wealth, and other family characteristics in 1993–1994, as well as schooling and income in 2014–2015 for 5, 421 children of those families. Using linear regressions and controlling for village or neighbourhood, as well as propensity score matching, we analysed breastfeeding associations for boys and girls separately, when regularly fed foods/beverages other than breast milk is significantly associated with years of schooling in 2014–2015 for girls, but not for boys, after controlling for the village or neighbourhood of residence in 1993–1994. For girls, ages 1 to 1.9, 2 to 2.9, 3 to 3.9, and >4 months, relative to ages <1 month, are associated with an additional 0.41 to 0.46 years of schooling, with p values of 0.086, 0.071, 0.043, and 0.026, respectively. No comparable estimate for boys attains statistical significance. Using propensity score matching yields similar results. Associations with annual income in 2014–2015 are not statistically significant, either for all children, or for either sex. Our finding suggests that delaying regular feeding of foods/beverages other than breast milk beyond 1 month may help girls' schooling but has no observable association with annual income, perhaps because of lower labour force participation by women. Also, the inclusion of controls for village or neighbourhood of residence reduces confounding.